4-(1,3-Diphenyl-4,5-dihydro-1H-pyrazol-5-yl)-1,3-diphenyl-1H-pyrazole - Fun, Hoong-Kun (International Union of Crystallography, 2011)
The title compound, C(30)H(24)N(4), contains two pyrazole rings and four phenyl rings. The pyrazole rings are essentially planar, with maximum deviations of 0.003 (1) and 0.066 (1) Å and make a dihedral angle of 73.43 (6)°. The two pyrazole rings make dihedral angles of 40.08 (6), 9.28 (6), 15.78 (8) and 17.25 (7)° with their attached phenyl rings. In the crystal, there are no significant intermolecular hydrogen-bonding interactions. The crystal structure is stabilized by C—H⋯π interactions.